GAMBARAN PENGETAHUAN TENTANG MEROKOK PADA ORANG TUA YANG MEMILIKI ANAK PEROKOK USIA 10-15 TAHUN DI DUSUN MODINAN BANYURADEN GAMPING SLEMAN - Nurmala Wulandari; Ni Ketut Mendri; Eko Suryani (Caring : Jurnal Keperawatan, 2017)
Based on Research (RisKesDa) on years 2013 Yogyakarta Special Region is a province with a prevalence of age ? 10 years each day smoking as much as 21.2%. There are many reasons teenagers or children age ? 15 years of smoking. The factor that causes the child to smoke are from the environment of smoking parents or peers and from the individual himself. This study was conducted to find out the description of parent's knowledge about cigarettes in parents own children smokers age 10-15 years in the Village Modinan. This research is a descriptive study using survey method. The sample was 38 respondents by using Purposive Sampling technique. Measuring tools using questionnaire. Parent's knowledge level on cigarettes in parents own had 10-15 year old smokers in 38 respondents showed that knowledge level was in good category. Obtained 60.5% of parents at the age of 36-45 years, 63.2% of parents have senior high school, 52.6% of parents work as housewife, and 55.4% of unemployed parrent. Knowledge of cigarettes in parents own have 10-15 year old smokers in Modinan Village mayority in the category of good knowledge.